Khyber Pakhtunkhwa’s Urdu Poem And Shehr e Ashob - Bashir, Sonia; Muhammad, Wali; Qarni, Muhammad Awais (sourcecoder, 2023)
The province of Khyber Pakhtunkhwa has been under the grip of terror and brutality for the past several decades. The physical and spiritual beauty of this territory has completely destroyed due to political and administrative failure and unrest. For several decades, this territory has been the target of known and unknown armed groups. As a result, the tragedy of this territory is richly reflected in the poetry and literature here. In modern literature, the poems of Shahr e Ashob are found in Ahmed Faraz, MohsinEhsan, KhatirGhaznavi, NazirTabasim, RiazSagar, Shujaat Ali Rahi, FarighBukhari, Izhar Allah Izhar, ShahabSafdar, Sajjad Babar and several other contemporary poets. In this research paper, the poets of Khyber-Pakhtunkhwa emerges in the city of Chaos, a map of a city which is on the target of oppression and tyranny, unrest, fear, desolation, material and spiritual misery. The poets of this region have effectively portrayed the emotions evoked by the beauty of the city and the calamities that befell it in the “shehirashoabs”resulting the tragic situation after the destruction of this smiling city. The researchers have analyzed the subject under research in a logical manner and have also given references to the poems of the poets of Khyber Pakhtunkhwa in this regard.